Character Education in Early Childhood Based on Kohlberg's Perspective - Sunaryo, Ilham; Fauziati, Endang (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2023)
Early Childhood learning prioritizes developing cognitive intelligence rather thanaffective intelligence or character building. This research is a type of exploratory descriptiveresearch. Exploratory descriptive research aims to describe the state of a phenomenon. Thisresearch is not intended to test certain hypotheses, only to describe what a variable, symptomor condition is. This research wants to further analyze related to early childhood charactereducation based on Kohlberg using literature studies obtained from various scientificsources. The urgency of character education for each individual is an absolute thing to do asan effort to build a generation that contributes to the progress of the nation. Charactereducation efforts certainly cannot escape from the psychological aspects contained inindividuals which may influence the process of achieving the success of character buildingitself. One of the most significant individual psychological aspects for the development ofindividual personality is the moral aspect.